1980
DOI: 10.1056/nejm198003273021304
|View full text |Cite
|
Sign up to set email alerts
|

Small-Airways Dysfunction in Nonsmokers Chronically Exposed to Tobacco Smoke

Abstract: We evaluated the effect of long-term passive smoking (involuntary inhalation of tobacco smoke by nonsmokers) and long-term voluntary smoking on specific indexes of pulmonary function in 2100 middle-aged subjects. Regardless of sex, nonsmokers chronically exposed to tobacco smoke had a lower forced mid-expiratory flow rate (FEF 25 to 75 per cent) and forced end-expiratory flow rate (FEF 75 to 85 per cent) than nonsmokers not exposed (P less than 0.005). In addition, values in passive smokers were not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(66 citation statements)
references
References 14 publications
6
59
0
1
Order By: Relevance
“…Supporting these deleterious effects of ETS, we found an increase in pulmonary function among 53 bartenders after reduction in workplace ETS exposure during an 8-week period (34). Two other observational studies demonstrated a relation between ETS exposure and decreased forced expiratory flow, midexpiratory phase (FEF 25%-75% ), but not FEV 1 or FVC (35,36). Other investigators have found no consistent relationship between ETS exposure and pulmonary function in adults (37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 65%
“…Supporting these deleterious effects of ETS, we found an increase in pulmonary function among 53 bartenders after reduction in workplace ETS exposure during an 8-week period (34). Two other observational studies demonstrated a relation between ETS exposure and decreased forced expiratory flow, midexpiratory phase (FEF 25%-75% ), but not FEV 1 or FVC (35,36). Other investigators have found no consistent relationship between ETS exposure and pulmonary function in adults (37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 65%
“…The differences between the areas were not noteworthy. For instance, measurements ranged from a 0.7 ppm average difference between smoking and nonsmoking cafeteria rooms (Fischer,et al 32 ) to about 3-5 ppm (White and Froeb 49 and Godin, et al 30 ). Indoor/ outdoor CO value differences were even less and ranged from no difference (Chappell and Parker 37 ) to the extreme of 9.5 ppm (Cuddeback, et al 35 ).…”
Section: Carbon Monoxidementioning
confidence: 99%
“…"8 White and Froeb found that nonsmokers who were chronically exposed to cigarette smoke in the workplace had levels of pulmonary function similar to that of light smokers and lower than nonsmokers in a smokefree environment. 9 Hirayama found a significantly increased risk of lung cancer for nonsmoking wives of heavy smok-…”
Section: Introductionmentioning
confidence: 99%